Pengaruh Disposisi Matematis Terhadap Kemampuan Pemecahan Masalah Matematika Pada Siswa Kelas VIII SMPN 1 Mataram Tahun Ajaran 2024/2025 - Anggia, Indry Puspita; Sripatmi, Sripatmi; Supiarmo, M. Gunawan (FKIP Universitas Mataram, 2025)
Based on the initial study, the mathematical problem-solving ability and mathematical disposition of eighth-grade students of SMPN 1 Mataram in the 2024/2025 academic year are classified as low. This study aims to determine the effect of mathematical disposition on mathematical problem-solving ability. The method used is quantitative with a comparative causal type (ex-post facto). The study population was 436 students, and a sample of 78 students was selected through a purposive sampling technique. The instruments used were a mathematical disposition questionnaire and a mathematical problem-solving ability test. The results of the descriptive analysis showed i) most students had high mathematical disposition (39 students); ii) most students had very high mathematical problem-solving ability (29 students); iii) most had high mathematical disposition with very high problem-solving ability (16 students). Based on a simple linear regression analysis, the equation , was obtained. This means that every 1 increase in mathematical disposition value will cause the mathematical problem-solving ability value to increase by 0.304. Hypothesis testing shows a significant influence between mathematical disposition and mathematical problem-solving ability. The coefficient of determination value is 0.289, indicating that mathematical disposition contributes 28.9%.